Red-emitting nano-porous 12CaO·7Al2O3:Sm3+ conductive phosphor for low-voltage field emission displays. (February 2017) - Zhang, Xinyang; Liu, Yuxue; Zhang, Meng; Yang, Jian; Zhu, Hancheng; Yan, Duanting; Liu, Chunguang; Xu, Changshan
Graphical abstract: Highlights: Red-emitting 12CaO·7Al2 O3 :Sm 3+ conductive phosphor has been prepared. The conductive performance of the phosphor originates from its encaged electrons. The conductive phosphor exhibits the enhanced red cathodoluminescence. The conductive phosphor shows the improved chromaticity coordinate. Abstract: A novel nano-porous 12CaO·7Al2 O3 :Sm 3+ conductive phosphor with red emissions has been prepared by a self-propagating combustion method in combination with subsequent treatments under different conditions. Upon 404 nm excitation, the phosphor shows four dominating red emission peaks at 564, 601, 648 and 709 nm, which are attributed to the 4 G5/2 → 6 H5/2, 6 H7/2, 6 H9/2, 6 H11/2 transitions of Sm 3+, respectively. The concentration-dependent luminescence of the phosphor shows that the dipole–dipole interaction is the major mechanism for the concentration quenching of red emissions of Sm 3+ ions in the phosphor. Absorption and electron spin resonance spectra indicate that the existence of encaged electrons in the phosphor plays a key role in the contribution to its conductive performance. Under electron beam excitation, the conductive phosphor exhibits the enhanced cathodoluminescence and the improved chromaticity coordinate compared to the insulating phosphor.